(untitled) (Research, Society and Development, 2022)
Precise real-time GNSS positioning, performed globally, unlike RTK and DGPS, requires the user to use only one receiver. However, it needs a global geodetic network to generate products such as precise orbits and satellite clocks. This type of positioning, when it also involves the use of the solution of phase ambiguities as integer values, is called PPP-RTK Positioning Technique. In 2011, Trimble introduced a real-time positioning service called Centerpoint RTX, which uses data from an active global GNSS network of 107 reference stations, along with innovative modeling and compression algorithms to calculate and relay precise satellite orbits. , as well as information and corrections regarding system clock and carrier wave phase ambiguities. Thus, the main objective of this work is to evaluate the accuracy of the PPP-RTK Positioning Technique, using corrections from the Trimble Centerpoint RTX Service in Brazil at three different convergence times. For this, GNSS surveys were carried out in all states of the Federation in SGB Stations, whose coordinates were considered as reference. Student’s t statistical tests were applied - to detect possible systematic errors in the data, and the Chi-Square test to assess the accuracy of the coordinates. Finally, the results indicate that the horizontal accuracy gradually improves with the increase in the convergence time, reaching 0.031 ± 0.007 (Trend and Accuracy) for 30 minutes of convergence.